Berberrubine protects against cisplatin-induced ototoxicity by promoting folate biosynthesis - Zhuang Miao; Danyang Chang; Xiaodong Du; Changling Sun (Frontiers in Pharmacology)
ObjectiveThis research investigated the possible shielding properties of BB (Berberrubine) against the harmful auditory effects of cisplatin, preliminarily delving into the underlying mechanisms responsible for this protection.MethodsHEI-OC1 cell viability was determined using a Cell Counting Kit-8 (CCK-8). The impact of BB on cochlear hair cells was studied through in vitro cochlear explants culture. Apoptosis levels were measured through Annexin V-PI, Cleaved Caspase-3, and TUNEL staining. The level of ROS (reactive oxygen species) was measured through the application of DCFH-DA, MitoSOX, and JC-1 fluorescent dyes for staining. Immunofluorescence analysis of cochlear samples from mice was conducted to quantify the hair cell count, and concurrently, ABR (Auditory Brainstem Response) testing was utilized to evaluate auditory function. The mechanism of action of BB was explored using RNA-Seq and qRT-PCR analysis.ResultsBB significantly improved cell survival rates under cisplatin treatment, reduced levels of apoptotic markers (TUNEL, Cleaved Caspase-3, Annexin V-PI), decreased ROS and MitoSOX levels, and improved JC-1 signals in both HEI-OC1 cells and cochlear hair cells in cochlear explants culture. Animal studies demonstrated that treatment with BB enhanced the survival of cochlear hair cells, reduced hearing impairment caused by cisplatin in mice. RNA-seq and qRT-PCR analysis revealed that BB influenced the expression levels of multiple genes (Ccnd2, Reln, Pgf, Mylk3, Ppplr12c, Thbsl), by promoting folate biosynthesis for hearing protection.ConclusionOur findings suggest that BB protects against cisplatin-induced hearing damage by enhancing folate biosynthesis, decreasing intracellular ROS levels, and inhibiting apoptosis.